2009
DOI: 10.1097/tld.0b013e3181b531da
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Learning in Youth With Traumatic Brain Injury

Abstract: Little is known about strategic learning ability in preteens and adolescents with traumatic brain injury (TBI). Strategic learning is the ability to combine and synthesize details to form abstracted gist-based meanings, a higher-order cognitive skill associated with frontal lobe functions and higher classroom performance. Summarization tasks were used to measure strategic learning ability through the production of abstracted gist-based concepts, and specific probes measured memory for explicit details. Twenty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 24 publications
3
46
1
Order By: Relevance
“…The findings related to generalization observed in this study suggest that a strategy-oriented approach to training could yield strengths similar to process training in terms of generalization when the strategies target complex functions that have ecological value. Furthermore, these findings raise the question of potential neural overlap in gist reasoning and executive functions as observed in our previous studies involving clinical populations (Ulatowska and Chapman, 1989;Gamino et al, 2009;Vas et al, 2009). It would be informative to discern the extent to which gist reasoning engages similar top-down cognitive control processes as the selected measures of executive function or alternatively the degree that gist reasoning incorporates components of executive function as basic building blocks.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The findings related to generalization observed in this study suggest that a strategy-oriented approach to training could yield strengths similar to process training in terms of generalization when the strategies target complex functions that have ecological value. Furthermore, these findings raise the question of potential neural overlap in gist reasoning and executive functions as observed in our previous studies involving clinical populations (Ulatowska and Chapman, 1989;Gamino et al, 2009;Vas et al, 2009). It would be informative to discern the extent to which gist reasoning engages similar top-down cognitive control processes as the selected measures of executive function or alternatively the degree that gist reasoning incorporates components of executive function as basic building blocks.…”
Section: Discussionmentioning
confidence: 77%
“…(Willis et al, 2006;Levine et al, 2007;van Hooren et al, 2007). For example, training that targets gist reasoning, defined as the ability to derive global meaning from explicit details, has been shown to improve meaning abstraction and other executive functions such as inhibition and working memory in clinical populations such as those with brain injury (Vas et al, 2009(Vas et al, , 2010, stroke (Ulatowska and Chapman, 1989), and attention deficit hyperactivity disorder (Gamino et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Evidence indicates that children who sustain a moderate or severe TBI in infancy or early childhood are particularly vulnerable to longer term consequences than are those who sustain injury later in childhood [17]. Chapman et al [18] reported that cognitive and language skills that are not developed at the time of the brain injury, or are in a stage of development, may be particularly vulnerable to long term sequel of TBI. Reliance on elements of orientation, even those most reliable for the child's age is inadequate for predicting broader cognitive and linguistic functioning.…”
Section: Discussionmentioning
confidence: 99%
“…The Pediatric CDE Workgroup recommends using the vocabulary subtest as a brief measure of language functioning. Although the WASI does not have specific sensitivity to mild injury severity, it has been shown to be sensitive to a range of neurologic conditions including moderateto-severe TBI (Gamino et al, 2009;Wechsler, 1999). Other Wechsler vocabulary scales have been used to measure language in children with TBI (Catroppa and Anderson, 2004;.…”
Section: Language and Communicationmentioning
confidence: 99%